Depressive symptoms and their association with chronic diseases in a high-Andean elderly community in Ayacucho, Perú - Custodio-Aulla, Kimberlyn K. (2026)
Objective: To determine the association between depressive symptoms and chronic diseases in older adults from an Andean community in Ayacucho, Peru, 2022. Methodology: Observational, analytical, cross-sectional study using secondary data from the Aunqui-Andes project, including 274 older adults in Totos, Cangallo, Ayacucho. Depressive symptoms were assessed with the Short Yesavage Geriatric Depression Scale, analyzed as a continuous (score 0-5) and a categorical (cutoff ≥3) variable. Chronic comorbidities were identified through self-reports and medical history. Generalized linear models with Poisson family and linear regression were applied to examine the relationship between comorbidities and depression. Results: The sample was predominantly female (59.9%), with a mean age of 74.5 years (SD: 7.1). No association was found between type of comorbidity and depressive symptoms. However, women showed a higher frequency (64.6%) of depressive symptoms compared to men (46.4%), with the highest prevalence in adults aged 71-80 years (57.9%). A significant relationship was observed between number of comorbidities and severity of depressive symptoms, with an increase of 0.23 points on the Yesavage scale per additional comorbidity (p < 0.001). This association was stronger in adults under 80 years, with an increase of 0.25 points. Conclusions: No association was identified between comorbidity type and depressive symptoms. Nevertheless, a higher prevalence was found among women, and the number of comorbidities was directly related to symptom severity, especially in non-octogenarian adults. These findings underscore the need for public health strategies focused on early detection and timely mental health interventions tailored to vulnerable individual and community needs.